Targeting the Protective Arm of the Renin-Angiotensin System to Reduce Systemic Lupus Erythematosus Related Pathologies in MRL-lpr Mice - Soto, Maira; Delatorre, Nicole; Hurst, Chelsie; Rodgers, Kathleen E. (Frontiers in Immunology, 2020)
Patients with Systemic Lupus Erythematosus (SLE) suffer from a chronic inflammatory autoimmune disease that results from the body’s immune system targeting healthy tissues which causes damage to various organ systems. Patients with lupus are still in need of effective therapies to treat this complex, multi-system disease. Because polymorphisms in ACE are associated with the activity of SLE and lupus nephritis and based on well-documented renal-protective effects of Renin Angiotensin System (RAS)-modifying therapies, ACE-I are now widely in patients with SLE with significant efficacy. Our research explores alternate ways of modifying the RAS as a potential for systemic therapeutic benefit in the MRL-lpr mouse model of SLE. These therapeutics include; angiotensin (1-7) [A(1-7)], Nor-Leu-3 Angiotensin (1-7) (NorLeu), Losartan (ARB) and Lisinopril (ACE-I). Daily systemic treatment with all of these RAS-modifying therapies significantly reduced the onset and intensity in rash formation and swelling of the paw. Further, histology showed a corresponding decrease in hyperkeratosis and acanthosis in skin sections. Important immunological parameters such as decreases circulating anti-dsDNA antibodies, lymph node size, and splenic follicle size were also observed. T cell activation was also ameliorated. The development of glomerular pathologies was also attenuated by RAS-modifying therapy. Improved number and health of mesenchymal stem cells (MSCs), as well as reduction in oxidative stress and inflammation may be contributing to the reduction in SLE pathologies. Several studies have already characterized the protective role of ACE-I and ARBs in mouse models of SLE, here we focus on the protective arm of RAS. A(1-7) in particular demonstrates several protective effects that go beyond those seen with ACE-Is and ARBs; an important finding considering that ACE-Is and ARBs are teratogenic and can cause hypotension in this population. These results offer a foundation for further pharmaceutical development of RAS-modifying therapies, that target the protective arm, as novel SLE therapeutics that do not rely on suppressing the immune system.